Evaluation of Agronomic Genotypes of Maize (Zea mays L.) under Agro-climatic Conditions during Kharif Season in Prayagraj, Uttar Pradesh, India - Manoj , Murugudu; Singh, Vikram; George, Shruti Grace (Emerging Issues in Agricultural Sciences Vol. 6, 2023)
This chapter find out the best Genotype among the maize hybrids, a field ex- periment was conducted during the kharif season of 2022 at the experimental field of the Crop Research Farm, Department of Agronomy, Naini Agricultural Institute, Sam Higginbottom University of Agriculture, Technology and Sciences, Prayagraj, Uttar Pradesh, India. All maize hybrids follow same pattern of development, although specific time and interval between stages and total number of leaves developed may vary between hybrids, seasons, time of planting and location. The longer maturity hybrid usually had grain yield advantage over earlier maturity hybrid when planting at early May, but the earlier maturity hybrid often showed a greater yield than longer maturity hybrid when planting was delayed. The experiment was laid out in a randomized complete block design which consisted of ten maize genotypes as treatments. The treatments were replicated three times. The significant difference in grain yield and other agronomic traits among various hybrids was due to the diverse background from which the hybrids were developed. The result of the study indicates that among different maize Genotypes, M-410 produced significantly higher plant height (218.35 cm), number of leaves per plant (15.60), dry weight per plant (152.24g), cob length (19.26 cm), number of rows per cob(14.85), number of grains per row ( 37.03), seed yield (9.54 t/ha) and stover yield (21.62 t/ha).. It was found more productive, when compared to others under agroclimatic conditions of Prayagraj, Uttar Pradesh. Since the future research is recommended to be conducted before recommending M - 410 genotype to farmer.